Application of Efferent Methods of Therapy in Complex Treatment of Patients with Diabetic Foot Syndrome (Genius Repository, 2023)
The clinical picture of purulent-necrotic lesions of the foot in patients with diabetes mellitus is characterized by an atypical course. The authors analyzed the results of treatment of 102 patients with diabetes mellitus who developed diabetic foot syndrome. Regional lymphotropic therapy and application sorption with polyphepane were included in the complex of treatment measures, which had a positive effect on the course of the disease. The obtained data indicate that the inclusion of RLAT, as well as the proposed efferent methods of therapy in the complex of therapeutic measures in patients with complicated diabetic foot, quickly stops the purulent process, prevents its generalization, and creates favorable conditions for the occurrence of reparative processes